Interdisciplinary aspects of possible negative effects of dogs on humans in Bosnia and Herzegovina - Muhamed Katica; Zarema Obradović; Nasreldin Hassan Ahmed; Enra Mehmedika-Suljić; Žana Stanić; Rowida Seifeldin Abdalaziz Mohamed; Emina Dervišević (Medicinski glasnik, 2020)
The coexistence of humans and dogs, in addition to all positive effects, can result in negative effects on human health. A particular risk is posed by a population of stray dogs, that is, dogs without owners and veterinary supervision. A contact with dogs in addition to bites, carries the risk of viral, bacterial and parasitic zoonoses, and can also cause psychological trauma. Children, the elderly and pregnant women are the categories most susceptible to the negative effects of dogs. The aim of the paper was to make an interdisciplinary analysis of the negative effects of dogs on humans. Dog bites cause wounds and dysfunction of damaged tissue, and often lead to various infections. The risks of rabies and tetanus are particularly significant if proper and timely treatment is not performed. Ongoing training for dog owners can significantly reduce the number of bites inflicted by owned dogs, but stray dogs remain a serious social problem and pose potential health risks of some zoonosis. Timely and adequate management of bite wounds and the use of rabies-post-exposure prophylaxis as well as psychotherapy , where indicated, significantly reduce possible adverse health effects for patients who have been bitten by dogs.
Keywords: canids; bites; risks; epidemiology; zoonosis